Pengembangan Kemasan Produk Berbasis Teknologi untuk Meningkatkan Nilai Jual di Pasar Global - Hidayah, Nischa Purnama; Susilawati, Sumita; Yustati, Herlina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Technology-based product packaging development involves using the latest innovations and technologies in designing, producing and managing packaging. By integrating technology in packaging development, companies can strengthen the position of their products in the global market and simultaneously increase consumer satisfaction. Innovation in efficient packaging can be a crucial factor for success in an increasingly competitive international market. This research aims to increase sales and packaging efficiency and provide more value to the products offered. The method used in this research is a qualitative approach with descriptive analysis. The results show that innovative packaging not only attracts the attention of consumers, but also adds significant value to the product and provides a positive impact of packaging designed with modern technology.